2020
DOI: 10.1186/s12876-020-01197-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of regional lymph node enlargement in patients with EGC within the expanded criteria for ESD

Abstract: AbstractsBackground: Lymph node (LN) metastasis is negligible in early gastric cancer (EGC) within expanded criteria for endoscopic submucosal dissection (ESD). However, regional lymph nodes in abdominal CT scans are sometimes enlarged in patients with EGC within the expanded criteria for endoscopic submucosal dissection (ESD). In this study, we investigated the clinical significance of regional lymph node enlargement on abdominal CT scan in patients with EGC within the expanded criteria for ESD. Methods: From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…According to epidemiological statistics, the recurrence rates of patients with stage-I and -II GC are about 10% and 30%, respectively [24]. At present, radical surgery, endoscopic mucosal resection (EMR), and endoscopic submucosal dissection (ESD) are alternative treatments for patients with GC invading the mucosa and submucosa [25][26][27]. However, developed countries such as South Korea and Japan are more inclined to ESD and EMR, while for developing countries in Southeast Asia and China, radical surgery is a more common choice.…”
Section: Discussionmentioning
confidence: 99%
“…According to epidemiological statistics, the recurrence rates of patients with stage-I and -II GC are about 10% and 30%, respectively [24]. At present, radical surgery, endoscopic mucosal resection (EMR), and endoscopic submucosal dissection (ESD) are alternative treatments for patients with GC invading the mucosa and submucosa [25][26][27]. However, developed countries such as South Korea and Japan are more inclined to ESD and EMR, while for developing countries in Southeast Asia and China, radical surgery is a more common choice.…”
Section: Discussionmentioning
confidence: 99%
“…The scoring system was then validated on 905 patients with non-curative ESD who declined surgery. 5-year cancer-specific survival was 99.6% in the low-risk group (60.4% of patients), 96% in the intermediate risk group (27.6% of patients) and 90% in the high-risk group (11.9% of patients), suggesting that ESD without additional surgical management may be sufficient in low-risk patients according to the eCura system[ 138 ].…”
Section: Endoscopic Treatment Of Gastric Neoplasiamentioning
confidence: 99%
“…These risk stratification tools are of particular importance when considering patients with radiologically enlarged lymph nodes that may or may not signify the presence of LNM. Lee et al [ 138 ] reported 47 cases of ESD for expanded criteria lesions, where patients had at least one enlarged lymph node on CT[ 138 ]. 12 of 47 patients had surgical resection, with no evidence of metastatic disease, while the remaining 35 patients had serial CT monitoring over a median 56 mo.…”
Section: Endoscopic Treatment Of Gastric Neoplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients' tumors only invade the muscle layer but have multiple lymph node metastases. Even if radical surgery, postoperative chemotherapy or preoperative neoadjuvant treatment is performed, their 5-year and 10-year survival rates are significantly reduced [ 12 , 13 ]. However, studies have shown that about 60% of GC has obvious tissue heterogeneity in transcriptomics sequencing, which makes it difficult to find molecules targeted at lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%